2019
DOI: 10.3892/ol.2019.10707
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatics analysis identifies hub genes and pathways in nasopharyngeal carcinoma

Abstract: The aim of the present study was to identify genes associated with and the underlying mechanisms in nasopharyngeal carcinoma (NPC) using microarray data. GSE12452 and GSE34573 gene expression profiles were obtained from the Gene Expression Omnibus (GEO) database. GEO2R was utilized to obtain differentially expressed genes (DEGs). In addition, the Database for Annotation, Visualization and Integrated Discovery was used to perform pathway enrichment analyses for DEGs using the Gene Ontology (GO) annotation along… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 66 publications
2
10
0
Order By: Relevance
“…Moreover, ATAD2 showed expression disturbance in hepatocellular carcinoma, ovarian cancer, stomach cancer, and other cancers (50)(51)(52). The discovery of Liu et al, through bioinformatics analysis, that ATAD2 may take part in the tumorigenesis of NPC is noteworthy (53). This also agrees with our ndings.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, ATAD2 showed expression disturbance in hepatocellular carcinoma, ovarian cancer, stomach cancer, and other cancers (50)(51)(52). The discovery of Liu et al, through bioinformatics analysis, that ATAD2 may take part in the tumorigenesis of NPC is noteworthy (53). This also agrees with our ndings.…”
Section: Discussionsupporting
confidence: 92%
“…Over the past few decades, microarray technology established using high-throughput platforms serves as a promising and efficient tool to detect phenotypic characteristics of cancer. [ 6 ] For example, Zhang et al [ 7 ] revealed that 8 genes and immune-related pathways associated with the development of osteosarcoma metastasis by weighted gene co-expression network analysis (WGCNA). Cai et al [ 8 ] and Lu et al [ 9 ] identified 5 hub genes as prognostic biomarkers for breast cancer metastasis by bioinformatics analysis.…”
Section: Introductionmentioning
confidence: 99%
“…There were several studies have previously identified many DEGs of NPC through bioinformatical analysis 50 - 52 . Compared with previous studies, the advantages of our study may be summarized as follows: Firstly, these previous reports have only screened core genes for NPC and they did not further evaluate the clinical value of core genes for NPC.…”
Section: Discussionmentioning
confidence: 99%